BRØDRE OG SØSTRE: Position og deltagelse på feltarbejdet - Whyte, Michael A. (Tidsskriftet Antropologi, 2019)
Michael A. Whyte: Brothers and Sisters - Position and Participation in Fieldwork. The author draws on fieldwork experience in Marachi Sub-Location in Western Kenya in order to explore some of the ways in which participation can shape - and be shaped by - a specific fieldwork. He takes the point of view of a brother looking at a sister and, through her, a relationship with another man. He traces his own developing appreciation of the complexity and the relativity of the exercise and how this perception inspired new paths of inquiry - which in tum led to other questions and other methods. He develops the paper in a series of vignettes - something about Marachi and something about the experience of a particular fieldwork in Marachi. In selecting from hisown experience he stresses the reflexivity inherent in fieldwork as process by speaking from a number of different positions. In an attempt to provide the reader with some stability in this shifting universe he retums periodically to an ethnographic position, providing analytical context and a more structured discussion of marriage, descent and affmity. This discussion, shaped both by the Africanist literature and the author’s experience of positioned participation, draws on other, more specific data-gathering exercises which will also be identified as parts of a process of understanding which inspires and is inspired by positioned participation. The point is to remind the reader that methodology is not simply a procedure for knowing but also a way of experiencing and a first step towards tuming experience into science. Taking a particular point of view has helped to make a shift from funetion to experience, and so to come to appreciate more direetly the immediaey of being in Marachi in 1978-79.